Usability of English note-taking applications in a foreign language learning context. Issue 1 (2nd January 2016) - Roy, Debopriyo; Brine, John; Murasawa, Fuyuki
Abstract : The act of note-taking offloads cognitive pressure and note-taking applications could be used as an important tool for foreign language acquisition. Its use, importance, and efficacy in a foreign language learning context could be justifiably debated. However, existing computer-assisted language learning literature is almost silent on the topic. This article reports on a controlled experiment introducing usability of note-taking applications (namely, Evernote, Memonic, SpringPad, Ubernote, and Keeppy) in English as foreign language (EFL) learning context. For pilot testing, 25 students had to complete five scenarios (text editing, entering persuasive content, sharing content, searching, and organizing) using Twitter as a tool similar to note-taking applications. Results suggest that the majority were comfortable with the tasks, although they could not complete all the tasks in the stipulated time, and certain tasks and features in Twitter caused difficulty for some students. The actual testing involved the 10 best candidates (based on their performance, when using Twitter) completing tasks (five scenarios similar to pilot analysis) with any two assigned note-taking applications, from a set of five. Participants were observed, video-recorded, and interviewed concurrently and retrospectively. They also completed perception-based questionnaires on the usability of the software. Data suggested that participants were comfortable opening accounts, typing in text, with general navigation, choosing photos, etc. A few features, such as web clipping and file uploading, caused problems for some participants. Most participants reported having no prior experience with any note-taking applications and that resulted in longer task completion time and errors. This study examines how technically oriented students reflect on using note-taking applications in an EFL learning context.